Understanding the beginning of diabetic nephropathy with electric potentials and repulsion forces around the renal glomerulus in the human kidney - Nieto Chaupis, Huber (2017)
Since the layers of the renal glomerulus play a crucial role as electric shield in the sense of stopping the pass of giant proteins like the albumin, in this paper we propose the idea that the very beginning of the renal failure of diabetic nephropathy might be explained with the laws of the electricity. Concretely, we focus on the presence of electric fields due to the flux of albumin through the glomerulus. For this end we propose the existence of the electric potential as ΦT = ΦA + λ ΦN the sum of the potentials of albumin and noise, respectively, and λ a parameter. From this, we have estimated the intensity of electric force from F =-ρ ▿ Φ T. The numerical results are consisting with the estimation of microalbuminuria as well as with the interpretation of the beginning of the renal failure in the sense that the presence of anomalous electric forces can be perceived as the anomalous functionality of the electric property of glomerulus.